Bridging the Gap Between Biofuels and Biodiversity Through Monetizing Environmental Services of Miscanthus Cultivation - Moritz Von Cossel; Bastian Winkler; Anja Mangold; Jan Lask; Moritz Wagner; Iris Lewandowski; Berien Elbersen; Michiel vanEupen; Stephan Mantel; Andreas Kiesel (Earth's Future, 2020)
Abstract Carbon neutrality in the transport sector is a key challenge for the growing bioeconomy as the share of biofuels has stagnated over the past decade. This can be attributed to basic economics and a lack of a robust market for these technologies. Consequently, more sustainable biomass supply concepts are required that reduce negative impacts on the environment and at the same time promote environmental services for sustainable agricultural cropping systems including erosion prevention, soil fertility improvement, greenhouse gas mitigation, and carbon sequestration. One promising concept is the cultivation of perennial biomass crops such as Miscanthus (Miscanthus Andersson) as biofuel feedstock. In this study, the multiple environmental services provided by Miscanthus are first explored and subsequently monetized. Then the integration of Miscanthus cultivation for biomass production into European agricultural systems is assessed. One hectare of Miscanthus provides society with environmental services to a value of 1,200 to 4,183 € a−1. These services are even more pronounced when cultivation takes place on marginal agricultural land. The integration of Miscanthus into existing agricultural practices aids both conservation and further optimization of socio‐economic welfare and landscape diversification. As these environmental services are more beneficial to the public than the Miscanthus farmers, subsidies are required to close the gap between biofuels and biodiversity that are calculated based on the provision of environmental services. Similar approaches to that developed in this study may be suitable for the implementation of other biomass cropping systems and therefore help foster the transition to a bioeconomy.